Perbedaan Jenis Crucible Pada Peleburan Sampah Aluminium Terhadap Waktu Peleburan Aluminium - Agung Purwo Prakoso (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2019)
Abstract Aluminum waste is a solid waste that is difficult to disentangle by the environment. Aluminum breakdown time ranges from 80-100 years. PT. Combiphar is a pharmaceutical industry whose production activities produce aluminum waste. Every week aluminum waste generation reaches 45 kg. Variations of crucible types, can result in different times. The crucible types used are stainless steel and graphite. The crucible type has good thermal conductivity. This type of research is experimental with post test design without control design. Aluminum trash comes from PT. Combiphar with the number of samples used is 2.07 kg. Based on the results of the study of 9 times reduction for 2 types of crucible crucible types of stainless steel and crucible types of graphite known that the type of crucible graphite faster melts aluminum waste with an average time of 45.78 minutes in 9 times repetition while the type of crucible stainless steel has an average The melting time 58.56 minutes in 9 repetitions.